A Web-based Framework for the Evaluation of End-User Experience in Adaptive and Personalised eLearning Systems - MULWA, CATHERINE; LAWLESS, SEAMUS; WADE, VINCENT; SHARP, MARY (IEEE, 2011)
The evaluation of interactive adaptive and personalised systems has long been acknowledged as a difficult, complicated and very demanding endeavour due to the complex nature of these systems. This paper describes a web-based framework for the evaluation of end-user experience in adaptive and personalised e-Learning systems. The benefits of the framework include: i) the provision of an interactive reference and recommendation tool to encourage the evaluation of systems that fulfil certain methodological requirements; ii) the collaborative nature of the framework facilitates the sharing of information among researchers from the information technology, adaptive hypermedia, information retrieval and e-Learning communities; iii) the identification of pitfalls in the evaluation planning process as well as in data analysis; and iv) the translation of presented information into users language of choice. This paper also presents a review of User-Centred Evaluation approaches, methodologies and techniques adopted by current systems and frameworks. The results of this review are analysed. From these results, an architectural design for the framework was specified.
International Workshop on Web Personalisation, Reputation and Recommender Systems, WPRRS 2011, at the IEEE/WIC/ACM International Conference on Intelligent Agent Technology
PUBLISHED
Campus Scientifique de la Doua, Lyon, France
Keywords: Computer Science and Engineering; Personalised e-Learning; adaptive hypermedia; Intelligent Content & Communications; Smart & Sustainable Planet